From implementation to impact : exploring the theories of change civil society organisation use to pursue community reconciliation - Sensabaugh, Kathleen Brittain (Department of Political Studies, 2016)
The central goal of this thesis is to explore the underlying theories and concepts that help to explain the step-by-step processes and form the foundations of reconciliation-based programmes in Cape Town, South Africa. In theory, civil society organisations (CSOs) have logical rationales of how their project designs lead to some form of reconciliation, but in practice, the links between project activities and project goals are very ambiguous and are seldom articulated in detail. Through empirical research, this thesis provides the explanation and articulation needed to link the goals and outcomes by applying strategies used in "theory of change" (TOC) discourse to two community reconciliation projects in Cape Town: the Community Healing Project housed under the Institute for Justice and Reconciliation, and the Healing of Memory workshops housed under the Institute for Healing of Memories. A TOC framework was first applied to community projects in the 1990s in the United States. The framework was designed to help explain the underlying theories that linked the activities to outcomes of community programmes that were established to tackle social issues on the community level. Seen as a success in explaining these projects, a TOC framework has been applied to several other community organisations, but has not been fully explored outside the Western context. The main goal of this research, then, is to apply a TOC framework to the two case studies and ascertain if it is a helpful tool in explaining community reconciliation interventions. The rationale for this research stems from the superficial engagement of the Truth and Reconciliation Commission (TRC) in South African communities, which resulted in a lack of healing and reconciliation at the community level. After the completion of the TRC, CSOs filled this gap in reconciliation by designing programmes to facilitate healing and reconciliation within communities. Years into the construction of such reconciliation projects, more information is needed about how the CSOs explain their programmes. The methodology for this research first involves an inductive approach that allows for observations about the activities and intended outcomes that make up the two case studies, then applies a TOC framework that allows for the explanation of the concepts that link the activities and outcomes. The research concludes that the application of a TOC framework to community reconciliation projects is not only a useful tool in helping to explain how the projects operate, but should be a necessary practice in explaining community reconciliation interventions because of its ability to describe the complicated phenomenon of reconciliation and avoid superficial explanations. By applying a TOC framework, the concepts and theories that lie behind the intervention strategies help to articulate why change happens the way it does.